Identification of the shadow economy determinants for the Eurozone member states: application of the MIMIC model - Remeikienė, Rita; Gasparėnienė, Ligita; Chadyšas, Viktoras; Cepel, Martin (Journal of Business Economics and Management, 2018)
This article is aimed at identification of the shadow economy’s causal factors and indicators in 19 Eurozone member states over the period from 2005 to 2016. Application of the MIMIC model has allowed to identify the following causal factors of the shadow economy in the Eurozone: employment rate, gender wage gap and income inequalities (expressed as the GINI index). All of these causal factors of the shadow economy in the Eurozone are attributable to the group of labour market determinants, which proposes that a reasonably arranged labour market mechanism can substantially diminish the probability of the shadow economy emergence. On the other hand, it has been found that the level of the shadow economy determines a positive/negative degree of the public trust in the EU authorities. The novelty of the research lies in the disclosure of the main causal factors of the shadow economy in the geographical area that covers different countries with a single currency. The findings of this research may contribute to the development of the shadow economy reduction strategies in 19 Eurozone member states.